Cardiac Differentiation of Pluripotent Stem Cells - Kristiina Rajala; Mari Pekkanen-Mattila; Katriina Aalto-Setälä (Hindawi Limited, 2011)
The ability of human pluripotent stem cells to differentiate towards the cardiac lineage has attracted significant interest, initially with a strong focus on regenerative medicine. The ultimate goal to repair the heart by cardiomyocyte replacement has, however, proven challenging. Human cardiac differentiation has been difficult to control, but methods are improving, and the process, to a certain extent, can be manipulated and directed. The stem cell-derived cardiomyocytes described to date exhibit rather immature functional and structural characteristics compared to adult cardiomyocytes. Thus, a future challenge will be to develop strategies to reach a higher degree of cardiomyocyte maturation in vitro, to isolate cardiomyocytes from the heterogeneous pool of differentiating cells, as well as to guide the differentiation into the desired subtype, that is, ventricular, atrial, and pacemaker cells. In this paper, we will discuss the strategies for the generation of cardiomyocytes from pluripotent stem cells and their characteristics, as well as highlight some applications for the cells.